Minority Dissent and Social Acceptance in Collaborative Learning Groups - Curşeu, Petru L.; Schruijer, Sandra G. L.; Fodor, Oana C. (Frontiers in Psychology, 2017)
The main aim of this paper is to test the extent to which social acceptance moderates the impact of minority dissent on group cognitive complexity (GCC). We hypothesize that divergent views expressed by a minority increase GCC especially when the group climate is open to divergent contributions (e.g., a socially accepting group climate). We also hypothesize that group size has a non-linear association with GCC in such a way that GCC increases as group size increases from low to average and then GCC decreases as group size further increases from average to high. We test these hypotheses in a sample of 537 students (258 women, with an average age of 23.37) organized in 92 groups that have worked together in the same group throughout the semester, and show that: (1) group size has a decreasing positive association with GCC, (2) both minority dissent and social acceptance are beneficial for GCC and (3) groups with the highest GCC are those that experience minority dissent and develop a socially accepting climate (in which group members can equally participate to the task), allowing the majority to process the dissenting views extensively.